E-082 Aggressive endovascular management of massive dural venous sinus thrombosis in the setting of acute myelogenous leukemia. (23rd July 2017) - Leonard, D; Haider, A; Thakur, R; Gottlich, C; Khan, U; Layton, K
Abstract : Introduction: Dural venous sinus thrombosis (DVST) accounts for less than 1% of all strokes. The presenting symptoms are diverse and include headache, blurred vision, diplopia, hemiparesis, aphasia, or even psychosis. Physical examination can demonstrate findings of increased intracranial pressure, papilledema, and distended scalp veins. The recommended treatment for DVST is anticoagulation; however, up to 13% have poor outcomes with anticoagulant therapy alone and more invasive endovascular therapies may be necessary. The prognosis of DVST has improved, with up to 79% experiencing complete recovery, though death and dependency rates vary from 13–28%. Methods: We present a 40-year-old woman, recently diagnosed with acute myelogenous leukemia (AML), who developed diffuse DVST. A literature review was conducted to determine current treatment guidelines, risk factors, and adverse events associated with the treatment of DVST. Results: Thirteen days into her treatment for AML, she began to complain of headache that was worse with coughing, blurred vision and difficulty reading. Initial head CT was negative. Her headaches and blurred vision continued for six days and she developed altered mental status. Ophthalmologic examination revealed bilateral papilledema with flame-shaped hemorrhages and a repeat CT demonstrated new hyperdensity suggesting DVST. Magnetic resonance venogram confirmed extensive thrombi throughout the entire dural sinus system. She was placed on an intravenous heparin infusion but her symptoms did not improve. Cerebral venography (CV) confirmed subacute pan-dural sinus thrombosis and a continuous microcatheter infusion of thrombolytic was begun. Multiple microcatheter rechecks with repositioning were performed over the next two days and revealed fluctuating areas of recanalization and rethrombosis without adequate venous outflow. The right transverse sinus was never crossed due to the organized clot in this segment and access to the superior sagittal (SSS) and left transverse (LTS) sinuses was always from the left internal jugular vein. She also underwent thrombectomy that successfully extracted large volume clot from the SSS and LTS. However, an underlying stenosis of the LTS required angioplasty and stenting in order to achieve good venous outflow. She was monitored in the intensive care unit and converted to enoxaparin sodium with headache improvement noted over the first week. However, recurrent headaches prompted a CT venogram several weeks later. There was a severe stenosis in the downstream end of the stent with recurrent obstruction and upstream venous pressure of 53 mmHg at the time of repeat microcatheter venogram. A second overlapping stent was required for definitive treatment and she was subsequently restarted on her chemotherapy regimen. Conclusion: DVST is an uncommon cause of stroke. The appropriate diagnosis is imperative as the treatment for DVS is vastly different from the treatment of arterial stroke. Patients who suffer from DVST have a good prognosis and often achieve complete recovery. This case demonstrates the utility of more invasive endovascular treatments for extreme cases that fail to improve, or worsen, following a trial of conventional care. When thrombolysis and thrombectomy alone were not successful, stenting of an underlying dural sinus stenosis was ultimately required for successful recanalization. Disclosures: D. Leonard: None. A. Haider: None. R. Thakur: None. C. Gottlich: None. U. Khan: None. K. Layton: None.